THE GREEN KEY TO SLO: EVALUATING ENVIRONMENTAL IMPACT AS A DETERMINANT OF SOCIAL LICENSE TO OPERATE - Kenzhetayev, Kanat (Nazarbayev University School of Sciences and Humanities, 2025)
This thesis looks at whether the environment can influence the Social License to Operate (SLO) in the industrial city of Oskemen, Kazakhstan. Using stakeholder theory, contractarianism, and environmental governance literature, the paper proposes and experimentally examines three hypotheses concerning the influence of environmental orientation, perceived benefit, proximity, trust, and justice on public willingness to grant SLO. By use of multivariate logistic regression models and original survey data (N = 118), the results refute the presumption that environmental concern is the main driver of SLO. Rather, perceived gain repeatedly turned up to be the best indicator of SLO granting; perceived fairness also had a noteworthy impact. There were no discernible moderating effects and environmental concern did not demonstrate direct or mediated effects via trust or justice. These findings imply that instrumental and procedural legitimacy exceed normative environmental orientation in determining public acceptability in environments burdened by pollution and economic dependence for the case of Oskemen. The paper ends by addressing post-Soviet implications for environmental governance, participative legitimacy, and industrial strategy.
ЗЕЛЁНЫЙ КЛЮЧ К ОБЩЕСТВЕННОМУ ДОВЕРИЮ: ОЦЕНКА ЭКОЛОГИЧЕСКОГО ВОЗДЕЙСТВИЯ КАК ФАКТОРА СОЦИАЛЬНОГО РАЗРЕШЕНИЯ НА ДЕЯТЕЛЬНОСТЬ
SLO-ҒА АПАРАР ЖАСЫЛ КІЛТ: ӘЛЕУМЕТТІК РҰҚСАТТЫ АНЫҚТАЙТЫН ЭКОЛОГИЯЛЫҚ ӘСЕРДІ БАҒАЛАУ
Keywords: Type of access: Open access; Social License to Operate; case study; environmental orientation; contractarianism.